Performance of asphalt mixture incorporating kaolin clay at different aging - Putra Jaya, Ramadhansyah; Haryati, Awang; Nur Amirah, M. S.; Mohd Khairul Idham, Mohd Satar; Haryati, Yaacob; Mohd Rosli, Hainin; Norhidayah, Abdul Hassan; Muhammad Naqiuddin, Mohd Warid; Abdul Rahim, A. H.; Mohd Rosli, M. H. (IOP Publishing, 2019)
In the fast-changing construction industry, the usage of natural material resources is tremendous. In order to comply with the demand of construction, waste materials have been used as a replacement of natural mineral resources. In pavement engineering, waste materials can be added into road composition. Kaolin clay is one of industrial waste materials successfully been used as a replacement of cement in concrete, but in the pavement, it has lack extensive study. In this investigation, kaolin clay partially replaced bitumen and the performance of aged asphaltic concrete AC14 were investigated. Kaolin clay replaced bitumen at 0%, 3%, 6% and 9% by weight of bitumen were used through this study. Tests conducted to measure the mixture performance were Marshall Stability, resilient modulus and dynamic creep test. Generally, it shows that the samples of unaged and long-term aging of asphalt mixture containing kaolin clay at 6% to 9% showed excellent, while 9% kaolin clay were most favorable for short term aging.